Leaf economics in a three-dimensional environment: Testing leaf trait responses in vascular epiphytes to land use, climate and tree zone - Richards, J. H.; Damschen, E. I.
1.The study of functional traits offers predictive power for community ecology. Particularly in cases where individual species are difficult to study, known properties of trait spectra, such as the leaf economics spectrum (LES), and trait-environment relationships can provide crucial generalizable information that can contribute to forecasts of distributional shifts in response to the abiotic effects of climate and land use changes. 2 Vascular epiphytes have been proposed as indicators of environmental change, but we know little about the ecology of most species. Key functional trait assumptions are based on terrestrial plants; testing these in epiphytes verifies their universality and will inform applying functional traits in predicting epiphyte responses to climate and land use change. 3 In this study, we use functional traits from 37 vascular epiphyte species from forests and shade coffee farms at two sites in northern Nicaragua. We compare correlations among traits and intraspecific trait variances with those of terrestrial plants and among epiphyte taxonomic groups. We also test trait responses to environmental differences between sites and land use types, and within zones of the tree. 4 We find that epiphyte leaf traits fall towards the slower end of the LES, but with about one-third lower leaf nitrogen per change in specific leaf area (SLA)relative to terrestrial herbaceous plants. Bromeliads show less relationship between these traits than other epiphyte groups and also deviate in other trait interrelationships, suggesting unique leaf construction. 5 Trait-environment relationships varied most strongly along vertical gradients within trees, but some traits, including SLA and carbon isotope ratio, also responded to land use and site differences. 6 We present evidence that trait relationships established for terrestrial plants appear to translate to epiphytes, but identify some possible caveats. Strong trait response to vertical gradients within trees suggests that within-canopy shifts could provide resilience to climate and land use changes for some epiphyte species.
Keywords: ABIOTIC CONDITIONS; CLIMATE CHANGE; ENVIRONMENTAL FILTERING; FUNCTIONAL TRAITS; INTRASPECIFIC VARIATION; LAND USE CHANGE; LEAF ECONOMICS SPECTRUM; TRAIT-ENVIRONMENT RELATIONSHIPS